Effects of Herbicides on Flowering. (29th April 2020) - Carpenter, David J.; Mathiassen, Solvejg K.; Boutin, Céline; Strandberg, Beate; Casey, Carlene S.; Damgaard, Christian
Abstract: Herbicides have been shown to reduce flower production and to delay flowering, with results varying among herbicides and tested plant species. We investigated the effects of herbicides on flowering in an extensive greenhouse study conducted in Canada and Denmark. The effects of low doses of 5 different herbicides (bromoxynil, ioxynil + bromoxynil, metsulfuron‐methyl, clopyralid, and glyphosate), simulating realistic drift scenarios (1 and 5% recommended field rates), on plant flowering were examined using 9 wild plant species exposed at either the seedling (6‐ to 8‐leaf) or flower bud stage. Following herbicide exposure, initial flowering date as well as flower production over time were recorded over the growing period. The effect of herbicides on cumulative flower numbers and flowering time were modeled using Gompertz growth models. Significant delays to peak flowering and/or reductions in flower production were observed in at least one plant species for all tested herbicides, with glyphosate often exhibiting the greatest negative effects, that is, plant death. Except for ioxynil + bromoxynil, there was no clear evidence of either the seedling or the flower bud stage being more sensitive. Overall, 58% of all species × life stage × herbicide treatments resulted in either a statistically significant or a strong decline in flower production with herbicide application rates up to 5% of recommended field rates, whereas significant or strong delays in peak flowering were also detected but were slightly less common. Effects at 1% label rates were minimal. Simultaneous delays to peak flowering and reductions in total flower production occurred in approximately 25% of all cases, indicating that herbicide application rates simulating realistic drift scenarios would likely have negative effects on wild floral communities. Environ Toxicol Chem 2020;39:1244–1256. © 2020 SETAC